Topoisomerase IV Bends and Overtwists DNA upon Binding - Charvin, G. (Biophysical Society, 2005)
Escherichia coli topoisomerase IV (Topo IV) is an essential ATP-dependent enzyme that unlinks sister chromosomes during replication and efficiently removes positive but not negative supercoils. In this article, we investigate the binding properties of Topo IV onto DNA in the absence of ATP using a single molecule micromanipulation setup. We find that the enzyme binds cooperatively (Hill coefficient α ∼ 4) with supercoiled DNA, suggesting that the Topo IV subunits assemble upon binding onto DNA. It interacts preferentially with (+) rather than (−) supercoiled DNA ([Formula: see text]) and more than two orders-of-magnitude more weakly with relaxed DNA ([Formula: see text]). Like gyrase but unlike the eukaryotic Topo II, Topo IV bends DNA with a radius R(0) = 6.4 nm and locally changes its twist and/or its writhe by 0.16 turn per bound complex. We estimate its free energy of binding and study the dynamics of interaction of Topo IV with DNA at the binding threshold. We find that the protein/DNA complex alternates between two states: a weakly bound state where it stays with probability p = 0.89 and a strongly bound state (with probability p = 0.11). The methodology introduced here to characterize the Topo IV/DNA complex is very general and could be used to study other DNA/protein complexes.